Alternatif Dispute Resolution to Reduce Costs, Energy, And Time Issued by DJP Taxpayer or Dispute Settlement in Taxation - Ghifari, Muhammad (KnE Social Sciences, 2024)
The tax revenue target which entailed by the Directorate General of Taxation (DJP) every year is always increasing. However, in the last 5 years tax revenues are not always achieved. One solution is to increase tax revenues by way of aggressive action against the taxpayer , which measures the tax collection by the law is carried out both persuasive and repressive. Tax collection action occurred because his existing differences in interpretation between the DJP as the agency authorized to issue Tax Assessment Letter (SKP) with taxpayer, as an individual or entity that receives SKP. If this happens, taxpayer can make legal effort to appeal to the tax court related to decisions made by the DJP. Taxpayer objection filed by the above decree issued by the DJP SKP is called the tax dispute. If the action taken by the DJP is very aggressive in terms of collecting tax revenue, it is thus a tax dispute that occurred in Indonesia will increase. Increasing cases of tax disputes would be costly, time, and effort both issued by the DJP or by taxpayer. One of the alternative solutions that may be made by both parties to get a Win-win Solution is to Alternative Dispute Resolution. Keywords: Tax; Tax Dispute; Alternative Dispute Resolution